Investigating the experiences of family caregivers who shackle people with mental disorders - Kusumawaty, Ira; Yunike, Yunike (Frontiers in Psychiatry, 2023)
The mental health literacy gap has resulted in shackled people with mental disorders being an alternative for family caregivers. Even though shackles violate human rights and affect physical and psychological health, it still occurs in particular countries for instance Indonesia. An in-depth study using the family function approach is needed to distinguish the components behind the application of shackles by families to find solutions to prevent restraint. This study investigates the in-depth experience of families with shackled family members. This qualitative research applies a phenomenological approach, involving eight family caregiver participants and living with the patient. Triangulation is conducted by applying four health cadres interviews to ensure the previous information. The process of in-depth interviews and observation method of collecting is completed until accomplished data saturation. The data analysis process uses Collaizi's pattern to formulate three main themes, the sanctuary as the ultimate solution for the family, the specifications of shackles, and the purpose of the family to carry out restraint. The conclusion is that shackles occur because of a lack of comprehension of the impact of shackles and the various limitations experienced, resulting in restraints being the final selection when handling patients. Peer support is essential for families to prevent shackles on family members with mental disorders. Technological advances become an inherent necessity in everyday life and must support family caregivers with mental disorders.